PROCESSING OF THE HYDROCARBON PART OF RECENTLY FORMED OIL SLUDGE BYLOW-TEMPERATURE PYROLYSIS METHO - GRYNYSHYN, OLEG; ZNAK, YURIY; CHERVINSKYY, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This paper presents an approach to the utilization of the hydrocarbon component of freshly formed oil sludges by applying the low-temperature pyrolysis method. The main advantage of this method is its versatility in processing raw materials regardless of their composition. The study used oil sludges that arose during the oil refining process at the enterprise PJSC "Naftokhimik Prykarpattya", located in the city of Nadvirna, Ivano-Frankivsk region. Pyrolysis was carried out in a laboratory batch-type installation at a temperature of 420°C in a sealed metal reactor equipped with a water condenser and a receiving flask. As a result of thermal destruction, three main products were formed: liquid pyrocondensate, solid residue in the reactor and gaseous products. The yield of the liquid fraction was 84.0% of the mass of the starting raw materials. The resulting pyrocondensate had a sulfur content of 0.95% by mass. and iodine number 61.5 g I2/100 g, which indicates the presence of unsaturated hydrocarbons. The low content of metals in the pyrocondensate and its fractions is a positive feature that facilitates the further use of the product in catalytic processes. The pyrocondensate was divided into fractions: gasoline, diesel and residual. To establish the potential areas of use of each fraction, their physicochemical properties were studied. The gasoline fraction is characterized by a high content of sulfur and unsaturated compounds, therefore it is advisable to use it as a component of motor gasoline after appropriate hydrotreating and reforming. The diesel fraction, similarly, after purification can be used for the production of commercial diesel fuel. The residual fraction is suitable for the production of fuel oil or as a component of lubricants. As for the solid pyrolysis residue, it is recommended to use it in road construction – in particular, for the formation of the lower layers of the roadbed. The proposed approach allows not only to effectively dispose of oil sludge, but also solves an important environmental problem, while increasing the resource base for the production of petroleum products.